Effect of single particle potential on total cross section of nuclear reaction - Yan Fan; WenJun Guo; ZiHan Xi (Physics Open)
In nuclear physics,the calculation of reaction cross-sections is an essential method for studying nuclear structure.By investigating the reaction cross-sections of different elements colliding with 12C and analyzing the data, insights into nuclear structure and the nature of interactions between particles can be gained.This study employs the Isospin Quantum Molecular Dynamics model (IQMD) to examine reaction cross-sections of collisions between various nuclei and 12C at specific energies.The calculated results show excellent agreement with experimental data. Using this method, reaction cross-sections for proton-proton,proton-neutron,and neutron-neutron interactions are computed. Subsequently,the same approach is applied to calculate the total cross-section of nuclear reactions between carbon isotopes. The research indicates that the magnitude of the total cross-section is influenced by the isospin effects of particles and is also correlated with the number of free neutrons and protons produced in the reaction.